A case report: EXTRAHEPATIC BILIARY CYSTADNOCARCINOMA ARISING FROM COMMON HEPATIC DUCT. - VIVITMONGKORNCHAI, Korkiat; HANDAGOON, Pim; LERTPRASERTSUKE, Nirush (The ASEAN Journal of Radiology, 2023)
A case of extrahepatic biliary cystadenocarcinoma arising from the common hepatic duct is reported. The sonographic, CT and ERCP appearances correlated well with the pathological findings. The typical imaging characteristics of biliary cystadenoma and cystadenocarcinoma especially the sonography and CT can lead one to the correct preoperative diagnosis even the tumor arising from the extrahepatic bile duct.